Correlating Melt Dynamics and Configurational Entropy Change With Topological Phases of AsxS100–x Glasses and the Crucial Role of Melt/Glass Homogenization - Chakravarty, Soumendu; Chbeir, Ralph; Chen, Ping; Micoulaut, Matthieu; Boolchand, Punit (Frontiers in Materials, 2019)
Melt dynamics and glass Topological phases of especially dry and homogenized binary AsxS100-x melts/glasses are examined in Modulated-DSC, Raman scattering and volumetric experiments. In the S-rich glasses (12%<x<23%), direct evidence for the elusive 537 cm-1 stretch vibrational mode of the Quasi-Tetrahedral (QT), S=As(S1/2)3, local structure is observed in FT-Raman scattering once melts are homogenized and glasses cycled through Tg+10˚C for an extended period. The enthalpy of relaxation at Tg, ∆Hnr(x), fragility index, m(x), Molar volumes, Vm(x) each display three distinct regimes of variation. Specifically, m(x) displays a Gaussian like global minimum (fragility window), and ∆Hnr(x) displays an abrupt square-well like variation (reversibility window), while Vm(x) displays a Gaussian-like local minimum (Volumetric window) in the isostatically rigid phase (22.5%<x< 28.5%). At low x (< 20%) in the Flexible phase, glasses are segregated with a S8-rich nanophase that decouples from the As-S glassy backbone. At medium x (22.5%<x<28.5%) glassy backbones form an isostatically rigid phase displaying a vanishing ∆Hnr(x) term, and compacted structures with corresponding melts being superstrong (m<20). At high x (28.5%<x<40%) in the Stressed-Rigid phase, glasses possess an increasing ∆Hnr(x) term, and melts become increasingly fragile, with m(x) > 20 as x increases. Taken together, these results underscore that superstrong melts yield isostatically rigid glasses, while fragile ones form either Flexible or Stressed-rigid glasses upon cooling. The onset of the rigidity transition near <r> = 2.22, instead of the usual value of <r> = 2.40, is identified with presence of QT local structures in addition to Pyramidal As(S1/2)3 local structures in the glassy backbone, and with a small but finite fraction of polymeric Sn chains being decoupled from the backbone.